Ilmu dalam Berbagai Peradaban - Mustaqim; Muhbib Abdul Wahab (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The history of science has a long journey. The progress of science is in line with the development of human civilization at that time. In the history of Ancient Civilizations such as Ancient Rome, Ancient Yuanani, Ancient India have given birth to very brilliant works and philosophers. The progress of science and technology today is evidence of the glory of past science. The purpose of this research is to describe the role of science in society and its development in ancient civilizations as well as the influence and contribution in the world of science today. The results showed that ancient civilizations have contributed greatly to world civilization, such as advances in science and technology, medicine, astronomy, mathematics and others. However, science in its journey experienced challenges and controversies including contradictions in religious and political beliefs but still developed to give direction to the world. And the legacy of science is a legacy of intellectual property to prepare ourselves to be more advanced in the future.